Intensitas Penyakit Utama pada Beberapa Klon Unggulan Tebu di Pabrik Gula Krebet Baru, Malang - Rizqiyah, Sakinah Inayatur; Yulianti, Titiek; Hidayat, Sri Hendrastuti (Jurnal Fitopatologi Indonesia, 2023)
Intensity of Main Disease in Several Superior Sugarcane Clones at Krebet Baru Sugar Factory, MalangSugarcane (Saccharum officinarum) is an important plantation crop in Indonesia as the major source of sugar production. Cane sugar production decreased significantly in recent years and it is not in line with its demand which is increasing from year to year. Many studies have been carried out to obtain sugarcane varieties which are expected to have high production and are resistant or tolerant to factors constraining crop production. Observations of the main sugarcane diseases, i.e. sugarcane streak   mosaic (Sugarcane streak mosaic virus/SCSMV), pokkah boeng (Fusarium moniliformae), and sugarcane smut (Sporisorium scitaminae) were carried out on 14 potential sugarcane clones in PG Krebet Baru, Malang. Observations of disease intensity were carried out every 2 weeks for 3 months and plant samples showing disease symptoms were brought to the laboratory to detect the cause of the disease.  Specific symptoms of sugarcane streak mosaic, pokkah boeng and sugarcane smut diseases were observed in the field involving mosaic, chlorosis on young leaves and smut, respectively. Mosaic symptom was found only on 3 clones with disease intensity ranging from 8.33% to 68.89%; whereas chlorosis and smut symptom was found on 11 and 14 clones with disease intensity ranging from 2.78% to 22.22% and 11.11% to 25%, respectively. Laboratory examination using the polymerase chain reaction method confirmed the presence of SCSMV; while the fungi F. moniliforme and S. scitamineum were confirmed through tissue isolation and observation of meristem tissue, respectively. In general, disease incidence was relatively low in clones 8 and 12 and these clones can be recommended as potential clones used in controlling the main diseases of sugarcane.